Effect of Formalin Fixation on Surgical Margins in Breast Cancer Surgical Specimen - Masooma Zaidi; Shaista Khan; Najiha Bilal Farooqi; Kashif Abbas; Romana Idrees (International Journal of Breast Cancer)
Margin analysis in breast surgery is an important predictor of local recurrence and can have vital impact on the postoperative treatment planning. Objective. The aim was to assess the mean reduction in the closest tumor-free surgical margin in millimeters of breast cancer specimens following formalin fixation. Materials and Methods. We conducted a cross-sectional study at the Aga Khan University Hospital from March 30, 2010 to January 20, 2011. One hundred consecutive breast tumour surgical specimens which had macroscopically visible tumour were included. The cancer type included both in situ and invasive cancers. Excluded were the patients who had previous surgery or systemic/radiation therapy. The closest tumor-free margin was recorded and compared with the margin after formalin fixation. P value of <0.05 was considered significant. Results. The mean age of our 100 patients was 53 years with the majority of the patients having undergone mastectomy for predominantly invasive ductal carcinoma. Following formalin fixation, the mean reduction of the closest tumor-free margin was noted as 2.14 mm which was found statistically significant. Conclusion. Considerable shrinkage of tumor-free surgical margins of breast cancer specimen was noted after formalin fixation. This inference can have implications on the postoperative management plan.